ANIMATION TEXT AS SPEECH GENRE AND WAYS OF HIS LANGUAGE REALIZATION - N. S. Kabylkina; T. N. Lomteva (Гуманитарные и юридические исследования)
In thе article states the results of the research project «The Lingvocultural dynamic of pragmatic effect of a phenomenon of play on words and its interpretation in receiving culture (on the basis of the American animation series of the end of XX - the beginnings of the XXI century)» which is devoted to research the lingvocultural dynamic of pragmatic effect of a phenomenon of play on words in the American animation. The article deals with generalization of the methodological bases of defining the genre of animation as a specific text type. Under investigation are also the ways of language representation of the text features determined by the author's intentions as a means of creating pragmatic effect.